2017
DOI: 10.1016/j.nucmedbio.2017.01.005
|View full text |Cite
|
Sign up to set email alerts
|

18 F-fluoro-2-deoxyglucose PET informs neutrophil accumulation and activation in lipopolysaccharide-induced acute lung injury

Abstract: Introduction Molecular imaging of the earliest events related to the development of acute lung injury (ALI)/acute respiratory distress syndrome (ARDS) could facilitate therapeutic development and patient management. We previously reported that 18F-fluoro-2-deoxyglucose (18F-FDG) PET identifies ALI/ARDS prior to radiographic abnormalities. The purpose of this study was to establish the time courses of 18F-FDG uptake, edema and neutrophil recruitment in an endotoxin-induced acute lung injury model and to examine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
30
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 45 publications
0
30
0
Order By: Relevance
“…In fact, pulmonary FDG kinetics are altered during both experimental and clinical ARDS. Therefore, FDG-PET has been proposed as a potential non-invasive method to provide comprehensive understanding of the mechanisms of ARDS, and help for early diagnosis and for evaluation of different therapeutic interventions [ 28 ]. Other techniques used PET with a sialic acid-binding immunoglobulin-like lectin 9 (siglec-9)-based imaging agent targeting vascular adhesion protein-1 (VAP-1) for quantification of regional pulmonary inflammation [ 29 ].…”
Section: The Open Lung Approach: Controversial Issuesmentioning
confidence: 99%
“…In fact, pulmonary FDG kinetics are altered during both experimental and clinical ARDS. Therefore, FDG-PET has been proposed as a potential non-invasive method to provide comprehensive understanding of the mechanisms of ARDS, and help for early diagnosis and for evaluation of different therapeutic interventions [ 28 ]. Other techniques used PET with a sialic acid-binding immunoglobulin-like lectin 9 (siglec-9)-based imaging agent targeting vascular adhesion protein-1 (VAP-1) for quantification of regional pulmonary inflammation [ 29 ].…”
Section: The Open Lung Approach: Controversial Issuesmentioning
confidence: 99%
“…]FDG-PET signal correlates with the presence of activated neutrophils(6). Clinical studies have also demonstrated that [ 18 F]FDG-PET imaging can be used to assess the neutrophilic inflammatory burden in the lungs in cystic fibrosis, pneumonia, and experimentally induced lung inflammation(6)(7)(8)(9). These results together indicate that [ 18 F]FDG-PET imaging can potentially be used to measure changes in pulmonary inflammation in response to anti-inflammatory treatments.We set out to explore 2 questions:(1) the utility of dynamic [ 18 F]FDG-PET acquisition in discriminating before and after O 3 exposure; (2) the feasibility of [ 18 F]FDG-PET in tracking the pathology of O 3 induced lung inflammation in in vivo O 3 models and their response over time (0, 24 and 28 h).…”
mentioning
confidence: 79%
“…]FDG-PET signal correlates with the presence of activated neutrophils(6). Clinical studies have also demonstrated that [ 18 F]FDG-PET imaging can be used to assess the neutrophilic inflammatory burden in the lungs in cystic fibrosis, pneumonia, and experimentally induced lung inflammation(6)(7)(8)(9).…”
mentioning
confidence: 99%
“…At 24 hours following GBCA injection, the blood content of Gd in LPS‐treated rats was approximately 44.7% higher than in control rats, although this difference was not significant. We have shown that a single high dose of LPS to rats results in multiple effects seen in septic patients, including pulmonary and neuroinflammation . It is possible that some degree of acute renal injury in the LPS‐treated rats during the first 24 hours after contrast injection could have resulted in higher GBCA levels in the blood and delivery to the brain, which may have normalized by 24 hours.…”
Section: Discussionmentioning
confidence: 99%